2013
DOI: 10.3390/fi5020113
|View full text |Cite
|
Sign up to set email alerts
|

A Concept for Support of Firefighter Frontline Communication

Abstract: In an indoor firefighter mission, coordination and communication support are of the utmost importance. We present our experience from over five years of research with current firefighter support technology. In contrast to some large scale emergency response research, our work is focused on the frontline interaction between teams of firefighters and the incident commander on a single site. In this paper we investigate the flaws in firefighter communication systems. Frequent technical failures and the high cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Current limitations in applications were eliminated by creating the content with GUI best practices [34,41], which involved dividing the content into zones containing primary, secondary, and tertiary content. Furthermore, functions that support personalized feedback were included, such as charts, statistics, and measurement reports.…”
Section: Discussionmentioning
confidence: 99%
“…Current limitations in applications were eliminated by creating the content with GUI best practices [34,41], which involved dividing the content into zones containing primary, secondary, and tertiary content. Furthermore, functions that support personalized feedback were included, such as charts, statistics, and measurement reports.…”
Section: Discussionmentioning
confidence: 99%
“…Communication was another significant challenge in emergency response [18,30,39,77,85]. Toups et al [85] identified two communication methods in the field: face-to-face interactions and shared radio communication.…”
Section: Related Work 21 Challenges Faced By First Respondersmentioning
confidence: 99%
“…Disaster related scholars have noted, however, that for some reason, since the 1970s, there has been little empirical support for the use of ICS to varying degrees by various organizations to classify international disasters. The organization and employment of all disaster response events across the country by ICS, regardless of their complexity, duration or size, is even less known [20,21]. Gregory et al conducted an inductive study of ICS use by fire departments and identified three main factors: structuring mechanisms, constrained improvisation and cognition management methods.…”
Section: Emergency Reesponse Plan Of the Incident Command Systemmentioning
confidence: 99%